Analisis Peran Diskusi Kelompok Dalam Kemampuan Penalaran Matematis Siswa Kelas IV Sekolah Dasar - Nabila, Mufthiri Silma; Aulia, Miftahul; Ermawati, Diana (Edu Berkah Khatulistiwa, 2024)
This research aims to describe the role of group discussions in improving the mathematical reasoning abilities of fourth grade students at SD N 2 Karangbener. Mathematics, as a mandatory subject at every level of education, is often considered scary, boring and difficult by most students, especially at the elementary school level. Difficulty learning mathematics hinders students' ability to solve everyday problems and develop their potential. The research method uses descriptive qualitative, with data collection techniques of observation, interviews and documentation. Observations were carried out by implementing direct learning practices in class using the group discussion method. Data were analyzed using qualitative data analysis methods, consisting of data reduction, data presentation, and drawing conclusions. The stratified subject-taking technique produced research results that showed the group discussion method was effective in improving students' mathematical reasoning abilities. Students involved in group discussions showed different understanding of concepts in indicators of mathematical reasoning ability such as SA who showed high ability and CE students with medium ability and EY with low ability in mathematics group discussions. The results of this research are that group discussions can improve students' mathematical reasoning abilities by paying attention to the role of each member in the group. This research contributes to educational practitioners to implement effective learning methods in developing students' mathematical reasoning abilities. The conclusion of this research shows that group discussions are effective in improving the mathematical reasoning abilities of class IV students at SD N 2 Karangbener. Through observations, interviews, and documentation, it was found that students who were involved in group discussions had a better understanding of concepts.